Fourth dose of COVID-19 vaccine: Does it still contribute any additional immunoprotection? - Rujittika Mungmunpuntipantip, PhD; Viroj Wiwanitkit, MD (Journal of Taibah University Medical Sciences, 2022)
A second booster dose of COVID-19 vaccine is a widely discussed issue globally. This letter to the editor describes on possible additional immunoprotection due to the fourth dose of COVID-19 vaccine. According to the modeling study, it can demonstrate that the fourth dosage of COVID-19 vaccination can still provide extra immunoprotection in case that previous doses are not the highly effective COVID-19 vaccines.